Influence of Citrate and Phosphate on the Adsorption of Adenosine-5′-Monophosphate at the Hematite Water Interface - Rakshit, Sudipta; Ray, Avedananda; Taheri, Ali; Essington, Michael E. (Frontiers in Environmental Science, 2022)
Nucleic acid derived organic phosphorus (Po) is an important source of plant available P when degraded to inorganic phosphate (P(V)i). It is known that when nucleic acids or components are adsorbed on mineral surfaces, the enzymatic degradation is hindered or delayed. Thus, understanding adsorption/desorption mechanisms of nucleic acids and their derivatives are key to assess the biogeochemical pathways of Po cycling. Here we report adsorption mechanisms of adenosine-5`-monophosphate (AMP) on hematite, a common iron oxide mineral, under various solution properties using macroscopic and in situ attenuated total reflectance Fourier transform infrared (ATR-FTIR) spectroscopic probes. The effects of citrate, mimicking organic acids from roots exudates, and the influence of P(V)i, representing inorganic fertilizer application, were also evaluated on the release of adsorbed AMP under various solution properties. The results indicated that AMP adsorbed with the hematite surface via the phosphate moiety, N7 atom and the π electron systems of the adenine moiety. The presence of citrate significantly decreased the AMP adsorption, which was also corroborated by the negative phosphate IR bands in the results of AMP and citrate competitive adsorption experiments monitored by in situ ATR-FTIR probe. Like citrate, P(V)i also reduced AMP adsorption on hematite. Our findings suggest a potential novel pathway of nucleic acid derived Po cycling in the soil environment.